2019
DOI: 10.1111/jocd.12859
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lactobionic acid peel, aluminum oxide crystal microdermabrasion, and both procedures on skin hydration, elasticity, and transepidermal water loss

Abstract: Summary Background Topical applications of alpha‐hydroxy acids and poly hydroxy acids in the form of peels gained popularity. To enhance the effect of these substances, aluminum oxide crystal microdermabrasion can be used in one procedure. Aims The assessment of skin hydration, elasticity, and TEWL after using lactobionic acid in the form of 20% peel and lactobionic acid in the form of 20% peel combined with aluminum oxide crystal microdermabrasion. Material and methods The study involved 20 Caucasian female s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 26 publications
0
25
0
Order By: Relevance
“…For example, it was reported that values of skin stiffness obtained with Cutometer correlate with age 7,11,30 . Accordingly, it was successfully used in the assessment of skin condition in both healthy 11,13,18,21,24 and affected by diseases groups 6,7 . In addition, in most studies, the Cutometer is used as a reference device with which other devices are compared 18,21,24 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, it was reported that values of skin stiffness obtained with Cutometer correlate with age 7,11,30 . Accordingly, it was successfully used in the assessment of skin condition in both healthy 11,13,18,21,24 and affected by diseases groups 6,7 . In addition, in most studies, the Cutometer is used as a reference device with which other devices are compared 18,21,24 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been extensively used in the medical research performed for estimation of progression of the skin diseases such as scleroderma, 2,3 systematic sclerosis 4,5 ichthyosis, 6 Werner Syndrome, 7 scars 8,9 or in order to show improvement after treatment 10 . Moreover, skin stiffness is also a good indicator to evaluate age‐related changes of skin often used in the cosmetic industry, 11 and frequently applied to estimate influence of cosmetics on state of skin 12,13 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond the skin surface, advanced sound and light‐based scanners, including ultrasound and optical coherence tomography (OCT), can evaluate epidermal and dermal ultrastructure, allowing for quantitative measurement of epidermal and dermal thickness, skin texture, dermal density (attenuation coefficient), vasculature and blood flow [9–12]. Skin function has been assessed by measuring skin secretions (moisture, pH, and sebum content), skin permeability (transepidermal water loss [TEWL]) and viscoelastic properties (elastic deformation laxity and stiffness) [9,13–16].…”
Section: Introductionmentioning
confidence: 99%
“…evaluates skin elasticity and hardness, [10][11][12][13] ultrasound elastography uses Young's modulus to describe tissue stiffness, 5,[14][15][16][17][18][19] DermaLab/ DermaLab Combo define elastic properties, [20][21][22][23][24][25] SkinFibrometer measures skin induration 5,[26][27][28][29] and most commonly used Cutometer measures skin elastic and viscoelastic properties. 5,7,10,26,[30][31][32][33][34] Suction methods are one of the most widely used in basic and in applied skin research. 5,35 The most commonly used and investigated device -Cutometer is based on suction method, it uses negative pressure to deform the skin mechanically.…”
mentioning
confidence: 99%